Mastering noninvasive predictive biomarkers to follow up renal transplant patients: non-invasive predictive biomarkers to renal transplant - Al-Talabani, Namama Soran; Ghoraishizadeh, Payman; Rachid, Shwan (Cellular and Molecular Biology, 2022)
Renal transplantation is the treatment of choice for end-stage renal disease (ESRD) patients. Several cellular processes are regulated via non-coding RNAs by silencing target gene expression. Previous investigations have established a linkage between a number of human microRNAs and kidney failure. This study aims to identify the expression of urinary miR-199a-3p and miR-155-5p as non-invasive biomarkers during post and pre-transplantation over a six-month follow-up period. In addition to the classic chronic renal disease markers (estimated glomerular filtration rate eGFR, Serum creatinine, serum electrolytes, and Antinuclear antibodies ANA test). Urinary miR-199a-3p and miR-155-5p expression levels in 72 adults with diabetic nephropathy and, 42 adults with lupus nephropathy renal transplant recipients. Both were compared with 32 healthy controls prior and post-transplantation. miRNAs were evaluated by quantitative reverse transcription-polymerase chain reaction. Urinary miR-199a-3p significantly (p<0.0001) downregulated in diabetic and lupus nephropathy prior to transplantation and significantly upregulated post-transplantation compared to the control. While urinary miR-155-5p quantities were significantly higher in prior renal transplant patients in comparison with the same patients’ post-renal transplantation(P<0.0001). In conclusion, Urinary miR-199a-3p and miR-155-5p can be used as a non-invasive biomarker with high specificity and sensitivity to follow up the renal transplant patients before and post-transplantation instead of biopsy which is complicated by a non-negligible factor.